Coronary arteritis as a cause of sudden cardiac death in a young girl - Purnima Paliwal; Swasti Jain; Arvind Ahuja; Sachin Mittal; Devender Singh Chauhan (University of São Paulo, 2021)
A case of probable coronary arteritis in a young girl who died suddenly and unexpectedly is presented. The histologic presentation of the disorder is discussed, especially the differential diagnosis of arteritis of the coronary arteries with an emphasis on tuberculosis (TB). TB myocarditis with or without concomitant lung involvement is rare, and tubercular coronary arteritis without underlying pulmonary Koch's disease is all the rarer. We herein describe a case where the cause of death was ascertained on post-mortem examination.